The ion channel narrow abdomen is critical for neural output of the Drosophila circadian pacemaker. - Lear, B.C.; Lin, J.M.; Keath, J.R.; McGill, J.J.; Raman, I.M.; Allada, R. (Neuron, 2005)
Circadian clocks consist of transcriptional feedback loops housed in interdependent pacemaker neurons. Yet little is known about the neuronal output components essential for rhythmic behavior. Drosophila mutants of a putative ion channel, narrow abdomen (na), exhibit poor circadian rhythms and suppressed daylight activity. We find that NA is expressed in pacemaker neurons and induced expression within circadian neurons is sufficient to rescue these mutant phenotypes. Selective na rescue in distinct pacemaker neurons influences rhythmicity and timing of behavior. Oscillations of the clock protein PERIOD are intact in na mutants, indicating an output role. Pore residues are required for robust rescue consistent with NA action as an ion channel. In na mutants, expression of potassium currents and the key neuropeptide PDF are elevated, the latter consistent with reduced release. These data implicate NA and the pacemaker neural network in controlling phase and rhythmicity.